POLA KOMUNIKASI INTRAPERSONAL UNTUK PENGEMBANGAN KEPERCAYAAN DIRI DALAM BERDAKWAH PADA MAHASISWA FAKULTAS DAKWAH IAI AL-AZIS - Naufal Ibnu Tsalis; Ahmad Asrof Fitri; Anjar Sulistyani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study examines the phenomenon of lack of self-confidence in students of the Faculty of Da'wah IAI AL-AZIS in preaching and conveying Islamic values. Intrapersonal communication, which includes introspection, self-reflection, and self-understanding, is identified as an important factor in developing self-confidence. The purpose of this study is to find out the intrapersonal communication patterns of students of the Faculty of Da'wah IAI AL-AZIS and how these patterns affect their increased confidence in preaching. This research uses a qualitative approach with in-depth interviews, observation, and documentation to collect data. The results showed that students of the Faculty of Da'wah IAI AL-AZIS developed intrapersonal communication patterns through activities such as contemplating, self-introspection, talking to themselves (inner monologue), and using external media such as mirrors, social media, books for self-reflection. Then the intrapersonal communication patterns formed include direct communication patterns which are a one-way process without feedback. The two-way process pattern and in this intrapersonal is a question and answer process within the individual. The pattern of reflection process using media as an external means. This communication pattern helps students build better self-confidence when preaching. In addition, Carl Rogers' self-concept theory is also applied in this process, including self-reflection, unconditional self-esteem, positive environmental acceptance, and behavior consistent with the real self. Keywords: Communication Patterns, Intrapersonal, Self-Confidence, Da'wah;